2006
DOI: 10.1073/pnas.0607142103
|View full text |Cite
|
Sign up to set email alerts
|

The wheat and barley vernalization gene VRN3 is an orthologue of FT

Abstract: Winter wheat and barley varieties require an extended exposure to low temperatures to accelerate flowering (vernalization), whereas spring varieties do not have this requirement. In this study, we show that in these species, the vernalization gene VRN3 is linked completely to a gene similar to Arabidopsis FLOWERING LOCUS T (FT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
1,050
3
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 934 publications
(1,093 citation statements)
references
References 40 publications
25
1,050
3
15
Order By: Relevance
“…RNA samples were extracted from leaves using the Spectrum Plant Total RNA Kit (Sigma-Aldrich). VRN1, VRN2, FT and ACTIN primers for SYBR GREEN quantitative PCR were developed in previous studies (10,70,71). VRN-A1, VRN-B1 and VRN-D1 expression was tested using genome specific qRT-PCR primers described before (69).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA samples were extracted from leaves using the Spectrum Plant Total RNA Kit (Sigma-Aldrich). VRN1, VRN2, FT and ACTIN primers for SYBR GREEN quantitative PCR were developed in previous studies (10,70,71). VRN-A1, VRN-B1 and VRN-D1 expression was tested using genome specific qRT-PCR primers described before (69).…”
Section: Methodsmentioning
confidence: 99%
“…The photoperiod and vernalization pathways converge at the regulation of FT1 (= VRN3 in wheat) (10), which encodes a mobile protein that travels from leaves to the shoot apical meristem (SAM) (11,12). Once in the SAM, FT1 becomes part of a florigen activation complex that binds to the VRN1 promoter, inducing its transcription (13)(14)(15).…”
mentioning
confidence: 99%
“…Three epistatic genes Vrn-H1 (Sgh2), Vrn-H2 (sgh1), and Vrn-H3 (Sgh3), located on chromosomes 5H, 4H and 7H, respectively, are responsible for the spring growth habit Komatsuda 2004, Takahashi andYasuda 1956). These genes are homologues of AP1, ZCCT and FT, respectively (Yan et al 2003(Yan et al , 2004(Yan et al , 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Flowering time and vernalization response are shared with wheat and the causal genes are located at conserved genomic regions ( Fu et al 2005;Turner et al 2005;Yan et al 2006;Beales et al 2007). Some disease resistance also shares conserved genetic elements in barley and wheat (Jordan et al 2010;Liu et al 2011;Silvar et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The vernalization genes (Vrn1, Vrn2, Vrn3) (Yan et al 2003(Yan et al , 2004(Yan et al , 2006 and the photoperiod gene (Ppd-H1) (Turner et al 2005) in barley have been cloned; their physiological and biochemical functions, along with their roles in genetic pathways leading to heading, are well documented. Previous conventional genetic studies identified some possible Eps loci including eam7 (syn ea7), eam8 (eak), eam9 (eac), and eam10 (easp), located on chromosomes 6HS, 1HL, 4HL, and 3HL, respectively (Gallagher et al 1991).…”
Section: Introductionmentioning
confidence: 99%